Pemberdayaan kelompok Karang Taruna Desa Pitumpidange melalui pembuatan Pasta Gigi ramah lingkungan - Rasmiati Rasmiati; Muhammad Jafar; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Vivi Elvira Ekawati; Andi Riska (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Eggshells are household waste often found in Pitumpidange Village and thrown away by the community. Eggshells consist of 94% CaCO3, 1% MgCO3, and 1% Ca3PO and the remaining 4% is organic matter which can be processed into environmentally friendly toothpaste. Apart from eggshells, another natural ingredient in toothpaste is betel leaf. It contains essential oils, catechins, and tannins which are polyphenol compounds and can act as an antiseptic and prevent the biological activity of caries-causing bacteria such as Streptococcus Mutants. The purpose of this Community Service is to overcome partners' problems, namely the accumulation of eggshell waste which is a crucial problem at the Karang Taruna Group in Pitumpidange Village. The program also increases the empowerment of partners through the manufacture of environmentally friendly toothpaste by utilizing the village's potential in the form of eggshells and betel leaves. Ten people are participating in this program. The community service implementation method consists of three main stages: counseling, training, and mentoring. A questionnaire containing statements about the partner's knowledge and skills after the program was implemented used to find out the partner's response to the program. The results of the community service activities show that the partners of the Karang Taruna group in Pitumpidange Village can process eggshells combined with betel leaves into environmentally friendly toothpaste. Therefore, this community service supports the implementation of village SDG goals and supports Indonesia in the G20 group (Group of Twenty) in utilizing the natural surroundings through green innovation.